Analysis of the Influence of Work Discipline, Work Environment, and Job Satisfaction on Employee Performance at the Military Court Office I-02 Medan - Yunita Arianty; Kholilul Kholik (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study uses an associative-quantitative approach with a multiple linear regression model. Data collection was carried out by distributing questionnaires. The results of the study indicate that Work Discipline, Work Environment and Job Satisfaction have a positive and significant effect on the performance of employees of the Medan I-02 Military Court Office both partially and simultaneously. Work Discipline has a partial positive and significant effect on the performance of employees of the Medan I-02 Military Court Office, where the t-count value is 3.485 and t-table 1.676 with a significant value of 0.001 which means the significant value is greater than 0.05 (0.001 <0.05). So H1 is accepted. Work Environment partially has a positive and significant effect on the performance of employees of the Medan I-02 Military Court Office where the t-count value is 3.687 and t-table 1.676 or t-count> t-table with a significant value of 0.000 which means the significant value is greater than 0.05 (0.000 <0.05). So H2 is accepted. Job satisfaction partially has a positive and significant effect on the performance of employees of the Medan I-02 Military Court Office, where the t-value is 4.745 and t-table 1.676 with a significant value of 0.000 which means the significant value is greater than 0.05 (0.000 <0.05). So H3 is accepted. Work discipline, work environment and job satisfaction together (simultaneously) have a positive and significant effect on the performance of employees of the Medan I-02 Military Court Office where the f-value is 102.824 and f-table or f-count> f-table = 102.824> 3.10 with a significant value of 0.000 which means the significant value is smaller than 0.05 (0.000 <0.05). So H4 is accepted